THE ROLE OF SELENIUM MICRONUTRIENTS AS ANTIOXIDANTS IN EXPOSURE TO E-CIGARETTE SMOKE - RIVAN VIRLANDO SURYADINATA; MERRYANA ADRIANI; SANTI MARTINI; SRI SUMARMI; BAMBANG WIRJATMADI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: E-cigarette products have resulted in various controversies concerning their posed impacts on health. Some argue that exposure to e-cigarette smoke could improve free radicals in the body; thus, it causes harming impacts on health. Peroral selenium (Se) administration can increase superoxide dismutase (SOD) and glutathione peroxidase (GPx) serving as antioxidants in the body. Methods: This research is an experimental study aiming to analyze the effectiveness of Se to decrease free radical due to exposure to e-cigarette smoke as one of the preventive actions. The research was carried out to male Wistar rats with exposure to e-cigarette smoke and peroral Se intake with different time and duration of administration. Results: Research results showed a decrease of antioxidant SOD and GPx in the administration of exposure to e-cigarette smoke, and they gradually increased after Se administration (p=0.000). Meanwhile, the malondialdehyde level was inversely proportional compared to antioxidant SOD and GPx. Conclusion: Se is a micronutrient that can reduce free radicals due to exposure to e-cigarette smoke through enhancement of antioxidant enzymes such as SOD and GPx.